Applying the sustainable knowledge and behavior to coffee roasters professional in the UAE - Kurniawan Arif Maspul (Peneliti Teknologi Teknik Indonesia, 2022)
The abundance of specialty coffee in the UAE has made this country one of the Meccas of coffee in the Middle East. Several national and global events have made the UAE a country visited by many global coffee professionals and professional coffee workers working in the UAE. One of the challenges is sustainability in the coffee production area, where the coffee roaster plays an essential role in maintaining consistency that is the benchmark and represents specialty coffee as one of the goals. Using the curriculum from the Specialty Coffee Association's Coffee Skills Program, the authors presented training and counseling to calibrate knowledge in roasting from the skills and behavior of coffee roasters to achieve sustainability in the coffee production area.